KOMUNITAS FUNGI MIKORIZA ARBUSKULA ASAL TANAH GAMBUT PADA JELUK BERBEDA HASIL PENANGKARAN INANG Zea Mays L. dan Pueraria Javanica. - Yusril, M; Burhanuddin, . (JURNAL HUTAN LESTARI, 2018)
Community of arburcular mycorrhizal fungi (AMF) trapped by twith Zea mays L. and Pueraria javanica from peat samples treated by water-table level difference. The objective of the study was to obtain AMF community resulted from trapping with the Z. mays. and P. javanica .This research was carried out for 3 months at screen house and Silviculture Laboratory Faculty of Forestry Universitas Tanjungpura. The research was conducted by using the completely randomized design (CRD). The results to found types AMF Glomus sp.1, Glomus sp.2, Glomus sp.3, Glomus sp.4, Glomus sp.5 and Glomus sp.6. Trapping with Z. mays on 20 cm Â was found AMF Glomus sp.1, Glomus sp.2, Glomus sp.3, Glomus sp.4, in 40 cm found AMF Glomus sp.1, and Glomus sp.4, while on the 60 cm obtained type AMF Glomus sp.1 and Glomus sp.2, for its spore density in the Z. mays. amounted to 843/300 g. Trapping results with P. javanica on 20 cm found AMF Glomus sp.1 type, Glomus sp.2, Glomus sp.3, Glomus sp.4, 40 found in type AMF Glomus sp.1, Glomus sp.3, Glomus sp .4 and Glomus sp.5, while on the 60 cm density obtained type AMF Glomus sp.1, Glomus sp.3, Glomus sp.4, Glomus sp.5, and Glomus sp.5 with total spores of spores of 207/300 g. The root samples of pueraria and maize plant colonization fall into the medium category with a root percentage of 30%.Keywords: Glomus spp. mycorrhiza, peat soils, trapping, water-table level.